UJI KOMPATIBILITAS KONSENTRASI SUSPENSI TEPUNG DAUN SIRIH HUTAN (Piper aduncum) DENGAN Trichoderma harzianum Rifai UNTUK MENGENDALIKAN PENYAKIT BUSUK BUAH KAKAO - Alpinsyah AD Ritonga; Muhammad Ali; Yunel Venita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Fruit rot diseaseasof cocoa is caused by the infection of Phytopthora palmivora. The diseas can cause a 50% reduction of cocoa yield. Control method that can be used is to combine a the botanical fungicide with antagonistic microbes which can be applied in disease control. The purpose of this study is to determine the compatibility of some concentrations of Betel leaves flour suspension with Tricoderma harzianum and to obtain the best combination to control diseases in cocoa fruits.Theexperimenthas been conducted experimentally using a Completely Randomized Design consisting of 5 treatments and 4 replications. The treatments were the concentration of suspension of betel leaves flour suspension with T. harzianum (0 g/l water + T. harzianum, 25 g/l water + T. harzianum, 50 g/l water +T. harzianum, 75 and 100 g/l water + T. harzianum).The data analyzed statistically with the analysis of variance and continuoudHonesty Significant Different (HSD) test at 5% level. The results indicated that the treatment of some suspension concentrations of betel leaves flour with T. harzianum is incompatible in controlling the P. palmivora fungus. Concentrations of suspension betel leaves flour of 100 g/lwater withT. harzianum showed the best ability to inhibit the growth of P. palmivora fungus on PDA medium, decrease the initial symptoms appereance of Cocoa fruit rot disease, and decrease the intensity of cocoa fruit rot disease by 33,87%. Keywords:       Compatibility, betel leaves flour, Trichoderma harzianum, Phytophthora palmivora